Trwanie rzeczy i trwanie kultury - Piłat, Robert (Załącznik Kulturoznawczy, 2015)
This article discusses the relation between temporal existence of things and the persistence of culture. The material and the immaterial aspects of culture are quite different in relation to time. According to philosopher Karl R. Popper, meanings, senses and ideas belong to a separate quasi-temporal realm of being. They come about in time but henceforth they exist non-temporarily. Their existence, unlike that of physical objects, does not depend on keeping a delicate balance between the change and identity − it is not based on struggle against time. But on the other hand, their seemingly atemporal subsistence is strictly connected to the temporal existence of things. The latter do not carry meaning in virtue of sheer convention, but rather by means of subtle connection between their material structure and the properties of sentient and intelligent beings. Books hold a very special place in this framework. The physical properties of books are intertwined with their content very strongly albeit mysteriously. It is safe to say that reducing books to their content − by conveying the content to digital carriers alone − would result in a serious impoverishing of culture. In reference to early journalist works by poet Zbigniew Herbert, three functions of preserving and studying artefacts are distinguished: reconstruction, preserving and learning. In such studies there is always a quest for originals and considerable efforts are made in order to distinguish them from copies and derivatives. The article gives a brief account of recent debate concerning the value of these pursuits. Finally a discussion with Michel Foucault is presented, concerning the role of things in self-formation